Modelagem e simulação numérica de escoamento sólido-fluido sobre meio poroso heterogêneo - Lima, Guilherme Hanauer de (2016)
During oil well drilling commonly the drilling fluid pressure in the well is greater than the pressure within the formation, which may cause the flow towards the porous substrate, a phenomenon referred to as invasion. The flow to porous formation carries particles which are retained by the substrate, through the filtration mechanism, originating a packed-bed of particles in the wall of the wellbore. In this paper, the mathematical and numerical model of particle flow through a porous channel positioned vertically is proposed. Increase in pressure loss caused by any obstruction of the flow through porous media due to deposition of particulate material is investigated. The porous substrate is represented by a heterogeneous model, which solid domain is described by disconnected cylinders. Porosity throughout the porous domain varies in the axial direction of the flow according to obstacle sizes, which are allocated in a staggered array. The analysis is performed in two steps. In the first, single-phase fluid flow allows the determination of permeability and pressure drop of the porous media. The second step is the process of particles deposition observed in two-phase flow into the porous substrate. Mathematical formulation and numerical modeling for particulate flow are represented by a Euler-Lagrange approach. The coupled solution of discrete phases (particles) and continuous (fluid) is performed by combining the models Dense Discrete Phase Model (DDPM) and Discrete Element Method (DEM). Results are obtained for a fluid with density and viscosity similar to a drilling fluid, with properties of a mixture with 37.3% of water and 73.7% of glycerin, the particles have diameters varying from 0.6 to 0.8 mm and the porosity of the porous medium is between 0.4 and 0.7. Results show that the diameter of the particles increase promotes the permeability reduction of the resulting medium formed by the porous medium and the particles bed. The increase of the injected particles concentration implies an increase in pressure drop, thus reducing the permeability through the channel. It is also observed that there is growth in the thickness of the bed with the increase of the concentration of injected particles.